Node Authentication in MANET by using Digital Group Signature with Elliptic Curve Cryptography - Dubey, Atul (International Journal of Computer Sciences and Engineering, 2019)
Security in the mobile ad hoc network is very challenging task due the open communication, absence of centralized control and authentication mechanism. In order to handle these security and reliability issues in the MANET (Mobile Ad hoc Networks), we have proposed a group digital signature and elective curve cryptography based modified AODV (Ad hoc On Demand Distance Vector Routing) routing protocol which provides authentication and reliable communication. Proposed digital group signature method has group manager which has administrative properties like to regulate the authentication mechanism and to handle the dispute or unauthorized node and it is able to check and verify the other node authenticity. We have tested our method on the basis of packet delivery ration, network throughput and the network load. Our approach will increase the transmission reliability and reduces the packet loss chance in comparison to existing approaches.